2022
DOI: 10.1186/s13048-022-00986-2
|View full text |Cite
|
Sign up to set email alerts
|

High expression of RIPK2 is associated with Taxol resistance in serous ovarian cancer

Abstract: Background Taxol resistance in serous ovarian cancer is responsible for its poor prognosis, yet the underlying mechanism is still poorly understood. Thus, we probed the mechanism of Taxol resistance in serous ovarian cancer with multiple bioinformatic methods to provide novel insights into potential therapies. Methods The differentially expressed genes (DEGs) in Taxol-sensitive and Taxol-resistant cell lines and their relationship with the overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Since HPV16-positive cervical cancer cells were more likely to undergo apoptosis when NOD1 was activated, this suggested that NOD1mediated apoptosis may help to prevent cervical cancer [34]. In contrast to Liu's result [34], NOD1 was shown to be significantly expressed in cervical squamous cell carcinoma (CSCC), and overexpression of NOD1 increased proliferation, invasion, and migration of CSCC cell lines by activating NF-κB and ERK signaling pathways and increasing IL-8 production [35][36][37].…”
Section: Colorectal Cancer (Crc)mentioning
confidence: 96%
See 2 more Smart Citations
“…Since HPV16-positive cervical cancer cells were more likely to undergo apoptosis when NOD1 was activated, this suggested that NOD1mediated apoptosis may help to prevent cervical cancer [34]. In contrast to Liu's result [34], NOD1 was shown to be significantly expressed in cervical squamous cell carcinoma (CSCC), and overexpression of NOD1 increased proliferation, invasion, and migration of CSCC cell lines by activating NF-κB and ERK signaling pathways and increasing IL-8 production [35][36][37].…”
Section: Colorectal Cancer (Crc)mentioning
confidence: 96%
“…Ovarian Cancer. According to Shen's research [36], serous ovarian cancer is resistant to taxol through the NOD1/RIPK2/NF-κB inflammatory pathway, and NOD1/ RIP2 promotes the growth of ovarian cancer by turning on NF-B signaling. However, they did not investigate if the effect is related to the microbiota in the ovary and the permeability of the ovarian wall, which might be disturbed by NOD1 expression [37].…”
Section: Colorectal Cancer (Crc)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, paclitaxel resistance is one of the primary factors for the poor prognosis. In a bioinformatics study searching for potential biomarkers associated with paclitaxel resistance in OC treatment, researchers found a correlation between the higher expression of RIPK2 and the development of paclitaxel resistance ( Shen et al, 2022 ). The mechanism leading to the resistance, for one thing, depends on the over-activation of RIPK2-mediated NF-κB signaling pathway, and another facet is the change of tumor microenvironment caused by RIPK2-mediated immune infiltration, including CD4 + memory T-cell, dendritic cells (DCs), common lymphoid progenitors (CLPs) ( Shen et al, 2022 ; Zhang and Wang, 2022 ).…”
Section: Manuscriptmentioning
confidence: 99%
“…In a bioinformatics study searching for potential biomarkers associated with paclitaxel resistance in OC treatment, researchers found a correlation between the higher expression of RIPK2 and the development of paclitaxel resistance ( Shen et al, 2022 ). The mechanism leading to the resistance, for one thing, depends on the over-activation of RIPK2-mediated NF-κB signaling pathway, and another facet is the change of tumor microenvironment caused by RIPK2-mediated immune infiltration, including CD4 + memory T-cell, dendritic cells (DCs), common lymphoid progenitors (CLPs) ( Shen et al, 2022 ; Zhang and Wang, 2022 ). Therefore, this makes sense to choose RIPK2 as a candidate target for OC, as RIPK2 inhibitors could be used in combination with chemotherapy agents to grapple with potential drug resistance and significantly ameliorate the original immune microenvironment that promotes tumor progression.…”
Section: Manuscriptmentioning
confidence: 99%